Zinc oxide nanomaterial and preparation method, electron transport film, light-emitting diode

By using lithium hydroxide and anhydrous zinc acetate to prepare zinc oxide nanomaterials in anhydrous and oxygen-free environment, the problem of poor dispersion stability is solved, the high dispersion stability and excellent film formation effect of nanomaterials are achieved, and the stable performance of optoelectronic devices is improved.

CN113809272BActive Publication Date: 2025-02-28TCL TECHNOLOGY GROUP CORPORATION
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202010546788.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-06-16
Publication Date
2025-02-28
Estimated Expiration
2040-06-16

AI Technical Summary

Technical Problem

The dispersion stability of existing zinc oxide nanomaterials is poor, which affects its film formation effect and performance in devices.

Method used

Lithium hydroxide and anhydrous zinc acetate are used as raw materials to prepare zinc oxide nanomaterials through thermal reaction in anhydrous and oxygen-free environment, and the reaction conditions are regulated to ensure the dispersion stability and film formation effect of zinc oxide nanomaterials.

Benefits of technology

The prepared zinc oxide nanomaterial has a small particle size (5-7 nanometers), good dispersion stability, wide energy gap, and can reach 3.7 eV. After application in optoelectronic devices, its stable performance can be effectively improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113809272B_ABST
    Figure CN113809272B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of light-emitting diodes, and in particular, relates to a method for preparing a zinc oxide nanomaterial, comprising the steps of obtaining a lithium hydroxide solution and anhydrous zinc acetate; mixing and dissolving the anhydrous zinc acetate and the lithium hydroxide solution in an anhydrous and oxygen-free environment, and then performing a thermal reaction to separate and obtain the zinc oxide nanomaterial. The method for preparing the zinc oxide nanomaterial provided by the present invention uses lithium hydroxide and anhydrous zinc acetate as raw materials, obtains the zinc oxide nanomaterial by thermal reaction in an anhydrous and oxygen-free environment, and reasonably regulates the reaction raw materials and reaction condition parameters, so that the particle size of the obtained zinc oxide nanomaterial is 5 to 7 nanometers, the particle size is small, the dispersion stability is good, and the energy gap is wide, reaching 3.7 eV.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of light-emitting diodes, and in particular relates to a zinc oxide nano material and a preparation method thereof, an electron transport film, and a quantum dot light-emitting diode. Background Art

[0002] Quantum dots have significant quantum dot confinement effects, which make them have the advantages of adjustable emission wavelength, narrow peak width, high luminous efficiency, long life, high thermal stability and excellent solution processability. They have broad application prospects in new display and lighting, solar cells, bio-markers and other fields. Quantum dot light-emitting diodes (QLEDs) prepared with more stable inorganic quantum dots as the light-emitting layer have the advantages of wide color gamut, saturated color, high color purity and low preparation cost, becoming a highly potential next-generation new display. After years of development and progress, the performance of QLEDs in all aspects, especially those prepared with alloy structures, has been greatly improved, especially the efficiency and life of red and green quantum dots can meet the requirements of commercial applications.

[0003] At present, zinc oxide nanomaterials are a kind of semiconductor oxide with a wide direct band gap, good chemical stability, and low growth temperature, and are widely favored by researchers. Zinc oxide, as a commonly used electron transport layer material in semiconductor photovoltaic devices or light-emitting devices, can significantly improve the recombination efficiency of carriers in the light-emitting layer of the device, and has a wide range of applications in the field of semiconductor devices. However, the zinc oxide nanomaterials currently used in the electron transport layer are generally prepared in the absence of metal doping, and the sample energy gap is about 3.5eV, which is still a certain gap from the energy gap corresponding to the intrinsic luminescence of zinc oxide crystal defects. However, high metal doping will affect the dispersion and concentration of the solution and cause phase change. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a zinc oxide nanomaterial, which aims to solve the technical problem that the existing method for preparing zinc oxide nanomaterials has poor dispersion stability.

[0005] Another object of the present invention is to provide a zinc oxide nanomaterial.

[0006] Another object of the present invention is to provide an electron transport film.

[0007] Another object of the present invention is to provide a quantum dot light emitting diode.

[0008] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a zinc oxide nanomaterial comprises the following steps:

[0010] Obtain lithium hydroxide solution and anhydrous zinc acetate;

[0011] In an environment without water or oxygen, the anhydrous zinc acetate and the lithium hydroxide solution are mixed and dissolved, and then a thermal reaction is carried out to separate and obtain the zinc oxide nanomaterial.

[0012] Correspondingly, a zinc oxide nano material is prepared by the above method.

[0013] Correspondingly, an electron transport film comprises the zinc oxide nanomaterial prepared by the above method or the above zinc oxide nanomaterial.

[0014] Correspondingly, a quantum dot light-emitting diode is provided, comprising an anode and a cathode arranged opposite to each other, a quantum dot light-emitting layer arranged between the anode and the cathode, and an electron transport layer arranged between the cathode and the quantum dot light-emitting layer; the material of the electron transport layer comprises the zinc oxide nanomaterial prepared by the above method, or comprises the above zinc oxide nanomaterial, or comprises the above electron transport film.

[0015] The preparation method of zinc oxide nano material provided by the present invention uses lithium hydroxide and anhydrous zinc acetate as raw materials, and obtains zinc oxide nano material by thermal reaction in anhydrous and oxygen-free environment. On the one hand, the present invention considers the adverse effects of water and oxygen on the stability of zinc oxide, adopts anhydrous zinc acetate as zinc source to synthesize in anhydrous and oxygen-free environment, removes moisture in the reaction system from the two aspects of raw material selection and process environment, avoids the hydrogen atoms of crystal water or water molecules in the system to form hydrogen bonds with the strong electronegative oxygen atoms in zinc oxide to cause the agglomeration phenomenon between zinc oxide molecules, thereby ensuring the dispersion stability of zinc oxide nano material and its film-forming effect on the device. On the other hand, taking lithium hydroxide with weak alkalinity as an alkaline solution precursor, it is possible to effectively regulate the intensity of the reaction, thereby regulating the generated particle size of zinc oxide nano particles, reducing the particle size of zinc oxide nano particles, both improving the band gap of zinc oxide and helping to improve the dispersion stability of zinc oxide nano material.

[0016] The zinc oxide nanomaterial provided by the present invention is prepared by the above method, has a smaller particle size of 5 to 7 nanometers, has good dispersion stability in the solution, and has a wide energy gap of up to 3.7 eV, which is closer to the energy gap corresponding to intrinsic luminescence. After being applied to optoelectronic devices, the stability performance of the optoelectronic devices can be effectively improved.

[0017] Since the electron transport film provided by the present invention contains the zinc oxide nanomaterial with small particle size, wide energy gap and good dispersion stability, the electron transport film has good film uniformity and stability, which is beneficial to improving the photoelectric stability performance of the device.

[0018] The quantum dot light-emitting diode provided by the present invention contains the zinc oxide nanomaterial with the above-mentioned particle size, wide energy gap and good dispersion stability, or contains the above-mentioned electron transport film with good film uniformity and good stability, so the photoelectric properties such as light brightness and efficiency of the quantum dot light-emitting diode are stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic flow chart of a method for preparing a zinc oxide nanomaterial provided in an embodiment of the present invention.

[0020] Figure 2 A quantum dot light emitting diode with a positive configuration is provided in an embodiment of the present invention.

[0021] Figure 3 A quantum dot light emitting diode with an inverted configuration is provided in an embodiment of the present invention.

[0022] Figure 4 It is the UV-visible test spectrum of the zinc oxide solution of Example 1 and Comparative Examples 1 to 3 of the present invention.

[0023] Figure 5 It is the appearance picture of the zinc oxide solution of comparative example 1 of the present invention (left) and the zinc oxide solution of comparative example 4 (right).

[0024] Figure 6 It is the appearance picture of the zinc oxide solution of comparative example 1 of the present invention (left) and the zinc oxide solution of comparative example 4 (right) under 365nm ultraviolet fluorescence. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and technical effect of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is described clearly and completely. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. In combination with the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0027] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0028] As attached Figure 1 As shown, an embodiment of the present invention provides a method for preparing a zinc oxide nanomaterial, comprising the following steps:

[0029] S10. Obtaining a lithium hydroxide solution and anhydrous zinc acetate;

[0030] S20. In an environment without water or oxygen, the anhydrous zinc acetate and the lithium hydroxide solution are mixed and dissolved, and then subjected to a thermal reaction to separate and obtain zinc oxide nanomaterials.

[0031] The preparation method of the zinc oxide nano material provided by the embodiment of the present invention uses lithium hydroxide and anhydrous zinc acetate as raw materials, and obtains the zinc oxide nano material by thermal reaction in an anhydrous and oxygen-free environment. On the one hand, the embodiment of the present invention considers the adverse effects of water and oxygen on the stability of zinc oxide, and uses anhydrous zinc acetate as a zinc source to synthesize in an anhydrous and oxygen-free environment, removes moisture from the reaction system from the aspects of raw material selection and process environment, and avoids the crystal water or hydrogen atoms of water molecules in the system to form hydrogen bonds with the strong electronegative oxygen atoms in zinc oxide to form agglomeration between zinc oxide molecules, thereby ensuring the dispersion stability of the zinc oxide nano material, and its film-forming effect on the device. On the other hand, taking lithium hydroxide with weak alkalinity as an alkaline solution precursor, the intensity of the reaction can be effectively regulated, thereby regulating the generated particle size of zinc oxide nano particles, reducing the particle size of zinc oxide nano particles, both increasing the band gap of zinc oxide and improving the dispersion stability of zinc oxide nano materials.

[0032] Specifically, in the above step S10, lithium hydroxide solution and anhydrous zinc acetate are obtained. In the embodiment of the present invention, lithium hydroxide and anhydrous zinc acetate are used as raw materials. If the alkaline precursor uses other hydroxides such as sodium hydroxide, or the zinc precursor uses other substances such as zinc acetate dihydrate, the particle size of the prepared zinc oxide nanoparticles will increase, the band gap will decrease, and it will be unfavorable to ensure the dispersion stability of the zinc oxide nanomaterial. The above-mentioned present invention can effectively regulate the particle size and energy gap of the zinc oxide nanomaterial by selecting the raw materials for preparation and controlling the reaction condition parameters, so as to obtain a zinc oxide nanomaterial with a small particle size, a wide energy gap and good dispersion stability.

[0033] In some embodiments, the step of obtaining the lithium hydroxide solution comprises: mixing the lithium hydroxide with an alcohol solvent, dissolving the lithium hydroxide in the alcohol solvent by ultrasound, stirring, etc., to obtain the lithium hydroxide solution. In some specific embodiments, after mixing the lithium hydroxide with the alcohol solvent, ultrasound is applied for 2.5 to 3 hours, and magnetic stirring is performed for 20 to 30 minutes to obtain the lithium hydroxide solution.

[0034] In some embodiments, the solvent in the lithium hydroxide solution is selected from at least one of ethanol, butanol, and pentanol. In the embodiments of the present invention, alcohol solvents such as ethanol, butanol, and pentanol are used as solvent components of lithium hydroxide and the reaction system, which have relatively good solubility for lithium hydroxide raw materials and generated zinc oxide nanoparticles.

[0035] Specifically, in the above step S20, in an environment without water and oxygen, the anhydrous zinc acetate and the lithium hydroxide solution are mixed and dissolved, and then a thermal reaction is carried out to separate the zinc oxide nanomaterial. In some embodiments, the step of mixing and dissolving the anhydrous zinc acetate and the lithium hydroxide solution and then carrying out a thermal reaction comprises: in an anhydrous protective gas atmosphere, the anhydrous zinc acetate is added to the lithium hydroxide solution at a temperature of 70 to 120° C. to form a mixed system, and then a thermal reaction is carried out for 10 to 20 minutes. In an embodiment of the present invention, on the one hand, in order to avoid the interference of water and oxygen on the stability of zinc oxide, the anhydrous zinc acetate and the lithium hydroxide solution are mixed and dissolved in a protective gas atmosphere such as dry nitrogen and argon, and then a thermal reaction is carried out. On the other hand, adding the anhydrous zinc acetate to the lithium hydroxide solution at a temperature of 70 to 120° C. is not only beneficial to improving the solubility of anhydrous zinc acetate in the lithium hydroxide solution, but also the high reactivity of hydroxide ions in the lithium hydroxide solution at 70 to 120° C. is beneficial to the dissolved zinc acetate reacting with hydroxide ions to generate zinc oxide nanoparticles. If anhydrous zinc acetate is added at a temperature lower than 70° C., the solubility of zinc acetate under this temperature condition is extremely poor, and the temperature is too low, the hydroxide ion reactivity in the reaction system is low, and insoluble byproducts such as zincous hydroxide are easily generated. If the reaction temperature is too high, the hydroxide ion activity in the reaction system is too high, and the reaction is too violent, which is not conducive to regulating the particle size and energy gap of the zinc oxide nanomaterial. In addition, by regulating the thermal reaction time to 10 to 20 minutes, the particle size of the generated zinc oxide nanoparticles and the energy gap of the zinc oxide nanomaterial are further regulated. If the reaction time is too low, the reaction is not sufficient, the yield of the zinc oxide nanomaterial is low, and the solution concentration is low, which cannot meet the application requirements of the device for the concentration of the zinc oxide nanomaterial; if the reaction time is too long, it is not conducive to regulating the particle size and energy gap of the zinc oxide nanoparticles. In some specific embodiments, under a dry protective gas atmosphere, the anhydrous zinc acetate is added to the lithium hydroxide solution at a temperature of 70°C, 80°C, 90°C, 100°C, 110°C or 120°C, and a thermal reaction is carried out for 10 minutes, 15 minutes or 20 minutes to separate the zinc oxide nanomaterial.

[0036] In some embodiments, in the mixed system, the molar ratio of lithium hydroxide to the anhydrous zinc acetate is (1-1.2):1. In the reaction system of the embodiment of the present invention, the molar ratio of lithium hydroxide to anhydrous zinc acetate is (1-1.2):1. If the lithium hydroxide content is too low, the zinc oxide yield is reduced; if the lithium hydroxide content is too high, the hydroxide ion concentration in the reaction system is enhanced, the alkalinity is too strong, the reaction rate is too fast, and the zinc oxide particle size cannot be effectively controlled, resulting in the generated zinc oxide nanoparticles having a large particle size and a reduced energy gap. In some embodiments, the concentration of the lithium hydroxide solution is 0.08-0.12 mmol / mL, and the lithium hydroxide solution of this concentration provides a suitable hydroxide ion concentration in the reaction system.

[0037] In some specific embodiments, under a protective gas atmosphere such as dry nitrogen, argon, etc., the anhydrous zinc acetate is added to the lithium hydroxide solution with a temperature of 70 to 120° C. and a concentration of 0.08 to 0.12 mmol / mL, and the molar ratio of the lithium hydroxide in the lithium hydroxide solution to the anhydrous zinc acetate is (1 to 1.2): 1. A thermal reaction is carried out for 10 to 20 minutes to separate and obtain the zinc oxide nanomaterial.

[0038] In some embodiments, the separation step includes: cooling the reaction system after the thermal reaction to below 10°C, and then using a precipitant and a dispersant to purify and separate the reaction system multiple times to obtain a zinc oxide nanomaterial. In the embodiment of the present invention, the reaction system after the thermal reaction is cooled to below 10°C, and a precipitant and a dispersant are used to purify and separate the zinc oxide nanomaterial generated in the system, thereby obtaining a purified zinc oxide nanomaterial. The low temperature environment is not only conducive to the sedimentation effect of the precipitant on the zinc oxide nanomaterial in the system, so that the zinc oxide nanoparticles are more fully precipitated, but also reduces the reaction between the raw materials and passivates the reaction of generating zinc oxide nanoparticles.

[0039] In some embodiments, the precipitant is selected from at least one of n-heptane, n-octane, n-hexane, and acetone. In some embodiments, the dispersant is selected from at least one of ethanol, butanol, amyl alcohol, toluene, chlorobenzene, and chloroform. The zinc oxide nanoparticles generated in the reaction system of the above embodiment of the present invention have poor solubility in the precipitant and good solubility in the dispersant. The purified zinc oxide nanomaterial is obtained by repeated purification with the dispersant and the precipitant.

[0040] In some embodiments, the reaction system after the thermal reaction can be cooled to below 10°C within 2 minutes (the cooling rate is about 30-40°C / min). By quickly cooling the reaction system to a low temperature environment below 10°C, the precipitation of zinc oxide nanomaterials is more conducive. In some specific embodiments, the reaction system after the thermal reaction is quickly placed in ice water for ice bathing, cooled to below 10°C, and then the reaction solution is transferred to a centrifuge tube, and at least one precipitant selected from n-heptane, n-octane, n-hexane, and acetone is added. The mixed solution is shaken and ice bathed for 30 minutes, and then the supernatant is centrifuged; the precipitate is dispersed with at least one dispersant selected from ethanol, butanol, amyl alcohol, toluene, chlorobenzene, and chloroform, and after mixing evenly, the supernatant is centrifuged again. Repeat the purification 2-3 times to obtain the purified zinc oxide nanomaterial. Among them, the centrifugal speed is 4000-6000rpm, and the duration is preferably 4-5 minutes.

[0041] The zinc oxide nanomaterials separated by purification in the embodiment of the present invention can be directly stored in a dispersant at a concentration of 15-20 mg / ml, which is not only conducive to improving the dispersion stability of zinc oxide nanoparticles, but also the zinc oxide nanomaterials at this concentration can be directly used for the deposition preparation of the electron transport layer of the device, and the application is flexible and convenient.

[0042] In some embodiments, the particle size of the zinc oxide nanomaterial is 5 to 7 nanometers. The embodiment of the present invention reasonably regulates the reaction raw materials and reaction condition parameters, so that the particle size of the prepared zinc oxide nanomaterial is 5 to 7 nanometers, with small particle size, good dispersion stability, and wide energy gap of 3.7 eV.

[0043] Correspondingly, an embodiment of the present invention further provides a zinc oxide nanomaterial, which is prepared by the above method.

[0044] The zinc oxide nanomaterial provided in the embodiment of the present invention is prepared by the above method, has a small particle size of 5 to 7 nanometers, has good dispersion stability in the solution, and has a wide energy gap of up to 3.7 eV, which is closer to the energy gap corresponding to intrinsic luminescence. After being applied to optoelectronic devices, it can effectively improve the stability of optoelectronic devices.

[0045] Correspondingly, an embodiment of the present invention further provides an electron transport film comprising the above-mentioned zinc oxide nanomaterial.

[0046] Since the electron transport film provided by the embodiment of the present invention contains the zinc oxide nanomaterial with small particle size, wide energy gap and good dispersion stability, the electron transport film has good film uniformity and stability, which is beneficial to improving the photoelectric stability performance of the device.

[0047] Correspondingly, an embodiment of the present invention also provides a quantum dot light-emitting diode, which includes an anode and a cathode arranged relatively to each other, a quantum dot light-emitting layer arranged between the anode and the cathode, and an electron transport layer arranged between the cathode and the quantum dot light-emitting layer; the material of the electron transport layer includes the above-mentioned zinc oxide nanomaterial, or includes the above-mentioned electron transport film.

[0048] The quantum dot light-emitting diode provided by the embodiment of the present invention contains the zinc oxide nanomaterial with the above-mentioned particle size, wide energy gap and good dispersion stability, or contains the above-mentioned electron transport film with good film uniformity and good stability, so the photoelectric properties such as light brightness and efficiency of the quantum dot light-emitting diode are stable.

[0049] In some embodiments, the quantum dot light emitting diodes described in the embodiments of the present invention are divided into positive structure and reverse structure.

[0050] In one embodiment, a positive structure quantum dot light-emitting diode comprises a stacked structure of an anode and a cathode arranged opposite to each other, a quantum dot light-emitting layer arranged between the anode and the cathode, and the anode is arranged on a substrate. Furthermore, a hole functional layer such as a hole injection layer, a hole transport layer, and an electron blocking layer may be arranged between the anode and the quantum dot light-emitting layer; an electron functional layer such as an electron transport layer, an electron injection layer, and a hole blocking layer may be arranged between the cathode and the quantum dot light-emitting layer. Figure 2 As shown, in some embodiments of positive structure devices, the quantum dot light-emitting diode includes a substrate, an anode arranged on the surface of the substrate, a hole transport layer arranged on the surface of the anode, a quantum dot light-emitting layer arranged on the surface of the hole transport layer, an electron transport layer arranged on the surface of the quantum dot light-emitting layer and a cathode arranged on the surface of the electron transport layer.

[0051] In one embodiment, the inversion structure quantum dot light emitting diode includes a stacked structure of an anode and a cathode arranged opposite to each other, a quantum dot light emitting layer arranged between the anode and the cathode, and the cathode is arranged on a substrate. Furthermore, a hole functional layer such as a hole injection layer, a hole transport layer, and an electron blocking layer may be arranged between the anode and the quantum dot light emitting layer; an electron functional layer such as an electron transport layer, an electron injection layer, and a hole blocking layer may be arranged between the cathode and the quantum dot light emitting layer. Figure 3 As shown, in some embodiments of the inversion structure device, the quantum dot light-emitting diode includes a substrate, a cathode arranged on the surface of the substrate, the electron transport layer arranged on the surface of the cathode, a quantum dot light-emitting layer arranged on the surface of the electron transport layer, a hole transport layer arranged on the surface of the quantum dot light-emitting layer, and an anode arranged on the surface of the hole transport layer.

[0052] In a further embodiment, the substrate layer includes a rigid substrate, a flexible substrate, etc.;

[0053] Anode includes: ITO, FTO or ZTO, etc.;

[0054] The hole injection layer includes: PEODT:PSS (poly (3,4-ethylenedioxythiophene): poly (styrene sulfonic acid)), WoO3, MoO3, NiO, V2O5, HATCN (2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene), CuS, etc.;

[0055] The hole transport layer can be either a small molecule organic substance or a high molecular conductive polymer, including: TFB (poly[(9,9-dioctylfluorenyl-2,7-diyl)-alt-(4,4'-(N-(4-n-butyl)phenyl)-diphenylamine)]), PVK (polyvinylcarbazole), TCTA (4,4',4"-tri(carbazole-9-yl)triphenylamine), TAPC (4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline]), Poly-TBP, Poly-TPD, NPB (N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine), CBP (4,4'-di(9-carbazole)biphenyl), PEODT: PSS, MoO3, WoO3, NiO, CuO, V2O5, CuS, etc.

[0056] The quantum dot light-emitting layer includes, but is not limited to: at least one of semiconductor compounds of Group II-IV, Group II-VI, Group II-V, Group III-V, Group III-VI, Group IV-VI, Group I-III-VI, Group II-IV-VI, and Group II-IV-V of the periodic table, or a core-shell structure semiconductor compound composed of at least two of the above semiconductor compounds. In some specific embodiments, the quantum dot light-emitting layer material is selected from: at least one semiconductor nanocrystalline compound of CdSe, CdS, CdTe, ZnO, ZnSe, ZnS, ZnTe, HgS, HgSe, HgTe, and CdZnSe, or at least two of the semiconductor nanocrystalline compounds of mixed type, gradient mixed type, core-shell structure type, or combined type. In other specific embodiments, the quantum dot light-emitting layer material is selected from: at least one semiconductor nanocrystalline compound of InAs, InP, InN, GaN, InSb, InAsP, InGaAs, GaAs, GaP, GaSb, AlP, AlN, AlAs, AlSb, CdSeTe, ZnCdSe, or at least two semiconductor nanocrystalline compounds of mixed type, gradient mixed type, core-shell structure type, or combined type. In other embodiments, the quantum dot light-emitting layer material is selected from: at least one of perovskite nanoparticle materials (especially luminescent perovskite nanoparticle materials), metal nanoparticle materials, and metal oxide nanoparticle materials. Each of the above quantum dot materials has the characteristics of quantum dots and good photoelectric properties. The thickness of the quantum dot light-emitting layer is 10 to 100 nm;

[0057] The electron transport layer comprises: the above-mentioned zinc oxide nanomaterial or the above-mentioned electron transport film;

[0058] The cathode includes: Al, Ag, Au, Cu, Mo, or alloys thereof.

[0059] In order to enable those skilled in the art to clearly understand the implementation details and operations of the present invention, and to demonstrate the significant improvement in the performance of the zinc oxide nanomaterial and the preparation method thereof according to the embodiments of the present invention, the above technical solutions are illustrated by multiple embodiments below.

[0060] Example 1

[0061] A zinc oxide solution (ZnO①), comprising the following preparation steps:

[0062] 1. In an argon glove box, first take 7 mmol of lithium hydroxide solid and dissolve it in 60 mL of ethanol solution, put it into a round-bottom flask and perform ultrasonic treatment for 3 hours. After the end, heat it to 80°C, cover the bottle with a stopper and stir it with a magnetic bar to obtain a lithium hydroxide precursor solution.

[0063] 2. Add 7.7 mmol of anhydrous zinc acetate solid into the lithium hydroxide precursor solution, maintain 80°C and stir with a magnetic stirrer for 20 minutes.

[0064] 3. After the reaction is completed, the round-bottom flask containing the mixed solution is quickly placed in ice water for ice bathing. After cooling to 10°C, it is divided into eight centrifuge tubes (7.5mL / tube) and 40mL of n-heptane is added. After the mixed solution is shaken, it is ice bathed for 30 minutes, and then centrifuged at 6000rpm for 5 minutes. After centrifugation, the supernatant is poured out and dispersed with 2.5mL / tube ethanol dispersant. The solutions after each two tubes of dispersion are combined into one tube, and 40mL of n-hexane is added to each tube. The solution is ice bathed again for 30 minutes and then centrifuged at 6000rpm for 5 minutes. After centrifugation, the supernatant is poured out and dispersed with 2mL / tube ethanol. Finally, the solutions after four tubes of dispersion are combined into one tube, and 8mL of zinc oxide ethanol solution is finally obtained.

[0065] Comparative Example 1

[0066] A zinc oxide solution (ZnO②) was prepared using commercial ZnO powder purchased from Sigma into a 30 mg / mL ethanol solution.

[0067] Comparative Example 2

[0068] A zinc oxide solution (ZnO③), which differs from Example 1 in that lithium hydroxide solid is replaced by sodium hydroxide solid, and all other aspects are the same.

[0069] Comparative Example 3

[0070] A zinc oxide solution (ZnO④), which is different from Example 1 in that anhydrous zinc acetate solid is replaced with dihydrate zinc acetate solid, and the other contents are the same.

[0071] Comparative Example 4

[0072] A zinc oxide solution (ZnO⑤), which differs from Example 1 in that anhydrous zinc acetate solid is replaced with anhydrous zinc chloride, and the other contents are the same.

[0073] Comparative Example 5

[0074] A zinc oxide solution (ZnO⑥), which differs from Example 1 in that anhydrous zinc acetate solid is replaced with anhydrous zinc nitrate, and the other contents are the same.

[0075] Comparative Example 6

[0076] A zinc oxide solution (ZnO⑦), which is different from Example 1 in that the anhydrous zinc acetate solid is replaced with anhydrous zinc stearate, and the other contents are the same.

[0077] Comparative Example 7

[0078] A zinc oxide solution (ZnO⑧), which differs from Example 1 in that the operation of "quickly placing the round-bottom flask containing the mixed solution in ice water for ice bathing" is omitted, and the other operations are the same.

[0079] Example 2

[0080] Quantum dot light-emitting diodes, the zinc oxide solution prepared in Example 1 is stored in a refrigerator, and the device is prepared once every 7 days using the same process as follows to obtain devices prepared by storing the zinc oxide solution for different times, including the steps of:

[0081] 1. Spin-coat a PEDOT:PSS:s-MoO3 hole injection layer on an ITO substrate and anneal in air;

[0082] 2. In a nitrogen atmosphere, spin-coat a 25nm PVK hole transport layer on the hole injection layer and anneal at 140°C;

[0083] 3. Spin-coat a 35nm CdSe@ZnS quantum dot light-emitting layer on the hole transport layer;

[0084] 4. The zinc oxide solution prepared in Example 1 was spin-coated on the quantum dot light-emitting layer on the 1st day, the 8th day, the 15th day and the 22nd day to form a ZnO electron transport layer with a thickness of 50 nm;

[0085] 5. Evaporate 100nm Ag electrode on the electron transport layer;

[0086] 6. After packaging, a positive structure QLED device is obtained.

[0087] Comparative Examples 8 to 10

[0088] The quantum dot light-emitting diode is different from Example 2 in that the electron transport layer is formed by depositing the zinc oxide solution prepared in Comparative Examples 1 to 3, and the rest are the same.

[0089] Furthermore, in order to verify the advancement of the method for preparing the zinc oxide nanomaterial according to the embodiment of the present invention, performance tests were performed according to the embodiment of the present invention.

[0090] Test Example 1

[0091] The present invention observed and tested the concentration of the zinc oxide solutions prepared in Example 1 and Comparative Examples 1 to 7. The zinc oxide solutions in Example 1 and Comparative Examples 1 to 3 were all clear dispersed solutions with a concentration of 30 mg / mL. However, the zinc oxide solutions (ZnO⑤ to ⑧) in Comparative Examples 4 to 7 were too turbid to be filtered and tested. Figure 4 As shown, the zinc oxide solution of Comparative Example 1 (left) is clear, while the zinc oxide solution of Comparative Example 4 (right) is obviously too turbid to be filtered for subsequent treatment. Figure 6 As shown, under 365nm ultraviolet light irradiation, light can enter the zinc oxide solution of Comparative Example 1 (left), while the zinc oxide solution of Comparative Example 4 (right) is too turbid and light cannot enter the interior of the solution, so subsequent treatment and application cannot be performed.

[0092] Test Example 2

[0093] The present invention tests the particle size and spectral performance of the zinc oxide nanoparticles in the zinc oxide solutions of Example 1 and Comparative Examples 1 to 3 respectively through DLS particle size test and UV-VIS (ultraviolet-visible) test.

[0094] The UV-VIS tests of Example 1 and Comparative Examples 1 to 3 are shown in the attached Figure 4 The DLS particle size test structure is shown in Table 1:

[0095] Table 1

[0096] sample Energy gap / eV Particle size 1 / nm Particle size 2 / nm Particle size 3 / nm Average particle size / nm ZnO① 3.7 6.33 6.32 6.31 6.32 ZnO② 3.53 14.65 15.39 15.60 15.21 ZnO③ 3.57 9.31 10.11 10.86 10.09 ZnO④ 3.52 13.05 13.41 13.80 13.42

[0097] From the above test results, it can be seen that the zinc oxide solution prepared in Example 1 of the present invention has a wider band gap of 3.7 eV, which is higher than the band gaps of Comparative Examples 1 to 3 and closer to the band gap corresponding to the intrinsic luminescence of zinc oxide crystals. In addition, the particle size is significantly smaller than that of the particles prepared in Comparative Examples 1 to 4, with an average particle size of only 6.32 nanometers. Small-sized zinc oxide nanoparticles have better dispersion stability and better film-forming performance.

[0098] Test Example 3

[0099] The present invention tests the brightness and external quantum efficiency (EQE) of the quantum dot light-emitting diodes prepared in Example 2 and Comparative Examples 8 to 10 every 7 days, and the test results are shown in Table 2 below:

[0100] Table 2

[0101]

[0102] From the above test results, it can be seen that the brightness and external quantum efficiency of the quantum dot light-emitting diode prepared by the zinc oxide solution of Example 1 every 7 days in Example 2 of the present invention are stable. Even if the device is prepared by using the zinc oxide solution placed for 22 days, its brightness and external quantum efficiency can maintain a high stability, indicating that the zinc oxide solution prepared in the embodiment of the present application has good dispersion stability, thereby improving the stability of the photoelectric performance of the device. However, the brightness and external quantum efficiency of the quantum dot light-emitting device prepared by the zinc oxide solution of Comparative Examples 6 to 8 significantly decrease as the solution is placed for a longer time, indicating that the dispersion stability of the zinc oxide solution of Comparative Examples 6 to 8 is poor.

[0103] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a zinc oxide nanomaterial, characterized in that: The following steps are involved: Obtain lithium hydroxide solution and anhydrous zinc acetate; In an anhydrous and oxygen-free environment, the anhydrous zinc acetate is added to the lithium hydroxide solution at a temperature of 70 to 120° C. to form a mixed system for mixed dissolution, and then a thermal reaction is performed for 10 to 20 minutes to separate and obtain a zinc oxide nanomaterial; the zinc oxide nanomaterial has the morphology of nanoparticles.

2. The method for preparing the zinc oxide nano material according to claim 1, wherein The anhydrous and oxygen-free environment is an anhydrous protective gas atmosphere.

3. The method for preparing the zinc oxide nano material according to claim 2, wherein: In the mixed system, the molar ratio of lithium hydroxide to the anhydrous zinc acetate is (1-1.2):1; and / or, The concentration of the lithium hydroxide solution is 0.08-0.12 mmol / mL.

4. The method for preparing the zinc oxide nano material according to claim 2 or 3, wherein: The solvent in the lithium hydroxide solution is selected from at least one of ethanol, butanol and pentanol; and / or, The protective gas is selected from at least one of nitrogen and argon.

5. The method for preparing the zinc oxide nano material according to claim 4, wherein: The separation step comprises: cooling the reaction system after the thermal reaction to below 10°C, and then purifying and separating the reaction system multiple times using a precipitant and a dispersant respectively to obtain a zinc oxide nanomaterial.

6. The method for preparing the zinc oxide nano material according to claim 5, wherein: The precipitant is selected from at least one of n-heptane, n-octane, n-hexane and acetone; and / or, The dispersant is selected from at least one of ethanol, butanol, amyl alcohol, toluene, chlorobenzene and chloroform.

7. The method for preparing the zinc oxide nanomaterial according to any one of claims 1 to 3 or 5 to 6, characterized in that: The particle size of the zinc oxide nano material is 5 to 7 nanometers.

8. A zinc oxide nanomaterial, characterized in that: The zinc oxide nanomaterial is prepared by the method according to any one of claims 1 to 7.

9. An electron transport film, characterized in that: The electron transport film comprises the zinc oxide nanomaterial prepared by the method according to any one of claims 1 to 7 or the zinc oxide nanomaterial according to claim 8.

10. A quantum dot light emitting diode, characterized in that: The quantum dot light-emitting diode comprises an anode and a cathode arranged opposite to each other, a quantum dot light-emitting layer arranged between the anode and the cathode, and an electron transport layer arranged between the cathode and the quantum dot light-emitting layer; the material of the electron transport layer comprises a zinc oxide nanomaterial prepared by the method of any one of claims 1 to 7, or comprises a zinc oxide nanomaterial as described in claim 8, or comprises an electron transport film as described in claim 9.

Citation Information

Patent Citations

  • Method for doping earth ions in zinc oxide nano crystal

    CN101993692A

  • Composite micro powder with hierarchical heterogeneous structure, and preparation method and application thereof

    CN109294229A

  • Method for repairing nano stick of zinc oxide in even diameter

    CN1686820A